Research on mixed gas filling process in laser transmission pipeline. (July 2020) - Xu, Zhenyuan; Ma, Wenjing; Zhang, Junwei; Xiang, Yong; Chen, Liangming
Abstract: Aiming at the problem of dynamic displacement of mixed gas in laser transmission pipeline, by selecting a typical section of the pipeline, the problem can be simplified to study the filling of binary mixed gas in a relatively closed cavity with the single entrance and exit. The finite volume method is used to simulate the flow field of this section of pipeline, and the velocity distribution of the binary mixed gas filling process is simulated by using the incompressible N-S equation and the standard k-epsilon turbulence model; the molar concentration distribution of the binary mixed gas over time is simulated. Furthermore, the distribution of flow field and the change of gas composition inside the pipeline were calculated under different inlet velocity conditions. Through the above simulations, the change of flow field distribution in the pipeline with time is described; the formation, development and extinction process of vortex at different time or at different positions in the pipeline are simulated. Based on the works above, the basic research idea and theoretical basis of the study on the mixed gas filling progress of large scale laser transmission pipeline are provided. By comparing and analyzing the characteristics of flow field distribution at different inlet velocity or at different time periods of the same inlet velocity, it will also have certain reference value to guide the implementation and optimization of the gas filling project of laser transmission pipeline.